Interactions of OXTR rs53576 and emotional trauma on hippocampal volumes and perceived social support in adolescent girls. (May 2020) - Malhi, Gin S; Das, Pritha; Outhred, Tim; Dobson-Stone, Carol; Bell, Erica; Gessler, Danielle; Bryant, Richard; Mannie, Zola
Highlights: In everyday life, social behaviour both influences, and is itself influenced by biology. The OXTR rs53576 is important for social behaviour and is expressed in the hippocampus. In adolescents with emotional trauma, OXTR rs53576 differentially affects hippocampal volumes. This interaction is associated with perceived familial and peer social support. This evidence indicates contextual hippocampal involvement in social behaviours. Abstract: Oxytocin (OXT) is a neuropeptide involved in social behaviour and is sensitive to environmental influences to alter individual vulnerability or resilience to stress resulting in both negative and positive outcomes. The effects of the OXT receptor ( OXTR) single nucleotide polymorphism (SNP) rs53576 on hippocampal and amygdala structure and functions in adults are differentially associated with susceptibility to adversity and social behaviours, but this evidence is lacking in healthy adolescents. Adolescence is a developmental period characterised by neurobiological and psychosocial changes resulting in higher susceptibility to mood disorders, particularly among girls. As the brain is highly plastic at this stage, to understand psychosocial and emotional development, clarity of the interactions between rs53576 and adversity on hippocampal and amygdala volumes and social behaviours is needed. In this study, we investigated the interactions between rs53576 and emotional trauma (ET) exposure on hippocampal and amygdala volumes of adolescent girls, and associations with parenting style, perceived social support and bullying behaviour. Based on an unbiased and corrected analytical approach, we found smaller left hippocampal volumes in higher (hET) compared to minimally (mET) exposed AA homozygotes, but no differences in G allele carriers nor in the amygdala. Within the mET AA group, larger volumes were associated with peer perceived social support, but in their hET counterparts, smaller volumes were associated with familial perceived social support. This evidence supports an important role for the hippocampus in social behaviours but extends current knowledge to suggest that hippocampal social behavioural features are contextually dependent on rs53576.